ANALISIS CITRA SOSIAL TOKOH UTAMA NOVEL LAYANGAN PUTUS KARYA MOMMY ASF - Rahmat Prayogi (Universitas Muhammadiyah Kotabumi, 2023)
Many negative prejudices arise when a woman becomes a widow. However, out there, many widows become single parents and successfully support their families without relying on a man. This is the issue in this research, which is how the image of the female main character in the novel